Digitalizing Islamic Pedagogy: The Role of Artificial Intelligence (AI) in Enhancing Student Motivation and Learning Effectiveness - Desta Ega Pratiwi; Siti Roudhotul Jannah; Jaenullah Jaenullah (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to describe the implementation of Artificial Intelligence (AI)-based Islamic Religious Education (PAI) learning media at SMP Negeri 1 Sekampung and analyze its impact on learning effectiveness and student motivation. The research is driven by the urgent need for pedagogical innovation to create interactive and contextual learning experiences that align with the digital generation's characteristics. Employing a descriptive qualitative approach, data were collected through observation, semi-structured interviews, and documentation involving school principals, PAI teachers, and students. The results indicate that integrating AI platforms such as Kahoot, Quizizz, and ChatGPT significantly increases student engagement and personalizes their understanding of Islamic concepts. The implementation follows a systematic process of integrating AI into lesson plans, interactive delivery, and automated evaluation providing instant feedback. Despite benefits, challenges such as infrastructure limitations, unstable internet, and the need for enhanced teacher digital competence were identified. In conclusion, AI-based media holds transformative potential to improve PAI learning quality, provided it is supported by adequate infrastructure, teacher training, and a strong emphasis on maintaining spiritual and moral values.